(untitled) (African Journal of Biomedical Research, 2024)
Teaching and learning process involves interaction between the teacher and the learner through various teaching methods which show what to teach, how to teach and the effects they will have on academic performance. This study investigated the effects of blended, and lecture teaching methods on students’ academic performance in research methodology. This was a non-randomized control trial quasi-experimental study. Total population of 96 students from two basic nursing schools in Enugu State assigned to experimental (BTM) and control (LTM) groups participated in the study. The demographic information was obtained using self developed demographic questions while validated achievement test on research methodology was administered before and after the intervention. Data analysis was carried out using Statistical Package for social sciences (SPSS) software version 25. BTM (pretest 43.70±9.20, 10.26% and 13.64%1st 2nd posttests, increase of 3.38% (P<0.05). LTM (pretest 44.68±9.59%, 48.25±6.30%, and 48.67±4.99% 1st 2nd posttests, increase of 0.43% (P>0.05). There was significant increase of 3.38% in the AP of basic nursing students after using blended teaching method in first and second posttests (P<0.05). There was increase of 0.43% in the AP after using LTM but not significant (P>0.05). There was statistically significant difference in the mean scores of pretests and posttests (P<0.05), of those exposed to BTM. BMT had a higher AP than LTM (P<0.05). BTM significantly improved AP while LTM showed least improvement on the AP of students in research methodology. BTM had positive effect in enhancing learning outcomes implying that students derive benefit from being taught using combined TMs.